Controlled Homoepitaxial Growth of Hybrid Perovskites. Issue 20 (2nd April 2018) - Lei, Yusheng; Chen, Yimu; Gu, Yue; Wang, Chunfeng; Huang, Zhenlong; Qian, Haoliang; Nie, Jiuyuan; Hollett, Geoff; Choi, Woojin; Yu, Yugang; Kim, NamHeon; Wang, Chonghe; et al.
Abstract: Organic–inorganic hybrid perovskites have demonstrated tremendous potential for the next‐generation electronic and optoelectronic devices due to their remarkable carrier dynamics. Current studies are focusing on polycrystals, since controlled growth of device compatible single crystals is extremely challenging. Here, the first chemical epitaxial growth of single crystal CH3 NH3 PbBr3 with controlled locations, morphologies, and orientations, using combined strategies of advanced microfabrication, homoepitaxy, and low temperature solution method is reported. The growth is found to follow a layer‐by‐layer model. A light emitting diode array, with each CH3 NH3 PbBr3 crystal as a single pixel, with enhanced quantum efficiencies than its polycrystalline counterparts is demonstrated. Abstract : Epitaxial growth of single‐crystal CH3 NH3 PbBr3 with controlled locations, morphologies, and orientations, using combined strategies of advanced microfabrication, homoepitaxy, and low‐temperature solution method is first reported. A light‐emitting diode array, with each CH3 NH3 PbBr3 crystal as a single pixel, with enhanced quantum efficiencies, is demonstrated.